Microbe Profile: Alteromonas macleodii − a widespread, fast-responding, 'interactive' marine bacterium. Issue 11 (30th November 2022) - Wietz, Matthias; López-Pérez, Mario; Sher, Daniel; Biller, Steven J.; Rodriguez-Valera, Francisco
Abstract : Alteromonas macleodii is a marine heterotrophic bacterium with widespread distribution − from temperate to tropical oceans, and from surface to deep waters. Strains of A. macleodii exhibit considerable genomic and metabolic variability, and can grow rapidly on diverse organic compounds. A. macleodii is a model organism for the study of population genomics, physiological adaptations and microbial interactions, with individual genomes encoding diverse phenotypic traits influenced by recombination and horizontal gene transfer.